2018
DOI: 10.1073/pnas.1721436115
|View full text |Cite
|
Sign up to set email alerts
|

Multidecadal, county-level analysis of the effects of land use, Bt cotton, and weather on cotton pests in China

Abstract: SignificanceChanges in land use, climate, and agricultural technologies affect pest severity and management. We analyzed long-term longitudinal data (1991–2015) on three major cotton pests for 51 Chinese counties. Bacillus thuringiensis (Bt) insect-resistant cotton had pervasive effects on the whole pest complex and its management. Adoption resulted in major reductions in insecticide use against bollworm. The resulting restoration of aphid biocontrol decreased aphid severity. Mirid bug severity increased, aide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 43 publications
2
63
0
Order By: Relevance
“…Schematic representation of the predicted PgCad1 protein in pink bollworm. The amino-terminal membrane signal sequence (S), cadherin repeats (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), membrane proximal region (MPR), transmembrane region (T), and cytoplasmic domain (C) are shown for the wild type (s, at top). Red numbers indicate deletions in the cDNA (108 bp) and 36 amino acids missing from the protein potentially encoded by the mutant allele r14 (bottom).…”
Section: Inheritance Of Resistance To Cry1ac and Cross-resistance To mentioning
confidence: 99%
“…Schematic representation of the predicted PgCad1 protein in pink bollworm. The amino-terminal membrane signal sequence (S), cadherin repeats (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), membrane proximal region (MPR), transmembrane region (T), and cytoplasmic domain (C) are shown for the wild type (s, at top). Red numbers indicate deletions in the cDNA (108 bp) and 36 amino acids missing from the protein potentially encoded by the mutant allele r14 (bottom).…”
Section: Inheritance Of Resistance To Cry1ac and Cross-resistance To mentioning
confidence: 99%
“…Faced with crippling control costs and the development by the pests of resistance to the pesticides used against them (2, 3), the Sudanese eventually resorted to the integrated pest management approach. A similar but more complicated series of events is described for the cotton fields of China in PNAS by Zhang et al (4), but in China it is not only trophic cascades leading to new pest upsurges but also effects of land-use alterations and climate change.…”
mentioning
confidence: 71%
“…So Zhang et al's (4) findings, based on analyses of a huge dataset of secondary data derived from 51 counties in eight provinces of China from 1991 until 2015, have important implications for many different cropping systems. Lu et al (5) had already pointed out the landscape-level effects of planting Bt cotton, but Zhang et al (4) show that it is also interactions of Bt cotton with climate change and land-use changes that are driving the emergence of novel problems. In some cases it has been beneficial because the lack of spraying, aided by warmer temperatures in May, has reduced populations of the cotton aphid A. gossypii, as these succumb to recovering natural enemy populations in concert with reductions in the bollworms.…”
mentioning
confidence: 99%
“…Maize production only had a positive effect on the abundance of A. lucorum in the later period. Combining these cultivated crops as a single landscape variable, our previous country-level analysis found that land use diversity (Shannon diversity) negatively affected mirid bug severity; the proportions of forest, water bodies, and unused land area were all negatively correlated with pest severity [42]. Here, we provided a more disaggregated cultivated land use classification, and estimated their effects separately on the population abundance of A. lucorum, revealing the functions of different host crops within a landscape more explicitly.…”
Section: Discussionmentioning
confidence: 97%